Hurdles and strategies in the teaching of algebra - Barnard, Tony, ....- (Leicester : Mathematical Asociation, 2005)
As all teachers of mathematics will know, the teaching of algebra is not straightforward and mistakes occur all too often. This book looks at, and tries to provide constructive suggestions to resolve, a wide range of errors. The bulk of the material in the book appeared in a series of articles published in Mathematics in School. It is hoped that the contents of this book will provide a stimulus for debate as well as constructive suggestions for dealing with tricky issues.
Keywords: Algebra; Wiskunde -- Secundair onderwijs